Biomedical Scholarly Article Editing and Sharing using Holistic Semantic Uplifting Approach - Asim Abbas; Steve Fonin Mbouadeu; Fazel Keshtkar; Joan DeBello; Syed Ahmad Chan Bukhari (Proceedings of the International Florida Artificial Intelligence Research Society Conference)
Efficient practices to provide access to biomedical publications facilitate the timely transfer of information from the scientific research community to peer investigators and other healthcare practitioners. At present, the portable document format (PDF) is one of the dominating formats to share scientific knowledge offline. Additionally, some HTML-based formats have been introduced to share scientific content online. Online Search engines, e.g., GoogleScholar, require machine-interpretable metadata to correctly index items in a context-aware manner for accurate biomedical literature searches. We have developed a lightweight technical infrastructure (goSemantically) and miniaturized that as Google Docs add-ons that helps authors to add machine-interpretable metadata at the content and structural levels while authoring biomedical content. The infrastructure uses the NCBO Bioportal resources to annotate the biomedical content with appropriate semantic vocabularies. It further utilizes the Schema.org meta tags and provides an intuitive interface for users to associate the semantics tags at the document level. Additionally, our infrastructure supports users in exporting their content in various online interoperable formats preserving the embedded semantics. As a result, the biomedical metadata content would easily be indexed by search engines, making them more favorable for semantic intelligence searches.